PERNIKAHAN KOMITMEN ILAHI PERSPEKTIF AL-MISBAH DAN AT-THABARI - Hidayah, Nurul (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2022)
This studi emphasize the importance of the concept of marriage that is tied up in an agreement, in the form of an ijab qobul which is made by a man before Allah witnessed is by the guardian’s parents of the woman he married. This research is based on the increasing number of divorces that occur in people’s live due to thw lack of understanding of the true nature of couple’s marriage. Therefore, the author considers that it is necessary to actualize the meaning of marriage which is implied in the bonds of divine commitment ( mitsoqon ghaliza). This study conclude that the marriage of divine commitment (mitsaqon gholiza) contained the interpretation of al-misbah and thabari is not only looking at the biological purpose in a maeeiage but rather the responsibility in a marriage by fulfilling the rights and obligations of each and creating harmonious relationship in order to achieve the saknah mawaddah warohmah family in the househould. So that the agreement can not be played because it will affect human life hereafter. Thistype of research use qualitative and research data comes from the library while the primary source data comes from the libarary while the primary source in this study is the interpretation of Ath-thabari and Al-misbah. The method used I the research in library ( libarary research) the data analysis method used in this research is descriptive analysis.